Ovascopic and hepatosonographic findings in a cow with concurrent infection of Paramphistome and Fasciola gigantica from Cauvery delta region of Tamil Nadu: Ovascopic and hepatosonographic findings in a cow with ——-Cauvery delta region of Tamil Nadu - Venkatesan, M; Latchumikanthan, A; Saravanan, M; Veeraselvam, M; Jayalakshmi, K; Vijayasarathi, M K; Meenakshisundaram, A; Yogeshpriya, S; Premalatha, N (Indian Journal of Veterinary and Animal Sciences Research, 2025)
A six years old Jersey crossbred cow was presented to Veterinary Clinical Complex, Veterinary College and Research Institute, Orathanadu, Thanjavur district with the history of jowl edema and voiding foul smelling diarrhoea for a month. On clinical examination of the cow, pale conjunctival mucous membrane, jowl edema, moist muzzle and watery malodorous diarrhoea, body temperature 38.4 0C, heart rate - 64 bpm, respiratory rate - 28 bpm were found. Ultrasonography of liver parenchyma showed hyperechoic small areas of hepatic parenchyma with dilated hepatic vein, portal vein and caudal vena-cava and gall bladder showed distension with presence of hyperechoic sediments. On cholecystocentesis under ultrasound guidance with 20 Gauge 1.5” needle at right costochondral junction at 9th intercostal space, collected bile sample revealed Fasciola gigantica eggs. Faecal examination revealed eggs of both Paramphistomes and Fasciola gigantica. Measurement of eggs of parasites was carried by micrometry which confirmed 151 x 72 μm size Amphistome eggs in feces and 162 x 91 μm size Fasciola gigantica eggs in both bile and fecal samples. The cow was treated with oxyclozanide @ 18mg/kg body weight orally and supportive therapy. Good improvement was noticed in the health status of the animal after treatment. Further examination of faecal samples from that animal did not show any parasite eggs on 15th, 30th and 45th day after treatment. In this study, ultrasonography of liver and gall bladder combined with faecal examination was helpful in detection of concurrent paramphistomosis and fasciolosis. The present case seems to be the first report of mixed infection of Fasciola sp and paramphistome in cattle from the Cauvery Delta region of Tamil Nadu.